PASAR MODAL REGIONAL DALAM MASA KRISIS FINANSIAL 1997 DAN 2007: KAJIAN TERHADAP INTERDEPENDENSI BURSA EFEK ASIA TENGGARA - Adwin Surja Atmadja (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
The devastating effect of the two world finansial crises had widely influenced not only on developed capital markets but also emerging ones, including the ASEAN regional markets. The crises have been commonly believed to have significant impact on the changing behaviour of the regional indices movements. This study investigates how the crises have affected the interrelation of stock indices’ movements amongst the five South East Asian countries. The multivariate time series analysis frameworks applied on series of the two sub-sample periods reveals the existing of a cointegrating relationship among the stock markets during the 1997 finansial crisis, but none of cointegrating vector to be found on the series of the 2007 crisis. The short run dynamic analyses conclude that the short run interrelation among the regional indices seems to be more intense during the 2007 finansial crisis period. For the latest period of crisis, the number of significant causal linkages between two variables on the series was greater than the other period. The analyses also show that the explanatory power of an endogenous variable to another in the system increased during the latest crisis, implying that the contagious effect of the crisis had increased the short run interdependence of the regional stock markets.